Libraries - Fühles-Ubach, Simone (Qualitative and Quantitative Methods in Libraries; Vol 6 No 2 (2017): June 2017 Issue, 2019)
The paper examines the role and position of libraries and their funding organisations from multiple perspectives. While customer orientation has become increasingly important for libraries for many years, their contribution to the overall corporate strategy has played a rather subordinate role. Libraries began defining their own library strategy very much oriented on user needs and by changing library services and products. What attracted less attention was the contribution of the library in achieving the overall corporate objectives of the funding organisations, i.e., its contribution to the company strategy. This is a critical point, because a visible and demonstrable contribution of the library characterizes the perception of top management. Does the library help achieve the long-term direction and goals of the institution? How can results be demonstrated? The paper addresses the different directions of communication that modern library management has to apply within the organisation. It is not only that embedded or liaison librarians are needed to firmly anchor the library in the centre of the institution. It is an embedded library as a whole that has to prove relevance and importance to the future of the institution. Without strong links to top management of funding institutions, even very well- performing libraries will stay at the periphery instead of at the centre of their institutions.